Preparation, antibacterial properties and heavy metals sorption of nanocomposites based on rice straw, Fe₃O₄ and polycaprolactone - Khandanlou, Roshanak (2015)
Since the availability of natural biofibers from renewable resources, the use of biocomposites is expanding in recent years. Rice straw as a natural fiber, is being used as a filler to improve the properties of polymer matrix and in biosorption of heavy metals. However, the yield of heavy metal removal by a natural fiber is low and separation of adsorbent from solution is difficult. The aim of this project was preparation of rice straw/Fe₃O₄ nanocomposite, studied its application in removal of heavy metals and used as a filler to improve the polymer properties. In this study, spherical Fe₃O₄ nanoparticles (Fe₃O₄-NPs) were synthesized on the surface of rice straw (RS). The optimum condition for the synthesis of Fe₃O₄-NPs on the rice straw surface is described in terms of the initial concentrations of FeCl₃.6H₂O and FeCl₂.4H₂O and volume of NaOH. The samples were studied using X-ray powder diffraction (PXRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), Fourier transform infrared spectroscopy (FT-IR), and vibrating sample magnetometer (VSM). The TEM images showed the mean diameters of Fe₃O₄- NPs in solid support decreased gradually from 18.47 to 9.93 nm with the increase of NaOH volumes. The VSM showed that the RS/Fe₃O₄-NCs has magnetic properties. The antibacterial activity of NCs indicated strong antibacterial activity against Gram-negative and Gram-positive bacteria, which was increased with the decreasing particle size. In addition, the suitability of the rice straw/Fe3O4 nanocomposites (RS/Fe₃O₄-NCs) for adsorption of Cu(II) and Pb(II) from aqueous solution was investigated. The ability of RS/Fe₃O₄-NCs for Cu(II) and Pb(II) adsorption was measured by atomic absorption spectroscopy (AAS). Various factors affecting the metal uptake behavior such as contact time, amount of adsorbent and initial concentration of metal ions were investigated using response surface methodology (RSM). The characteristic parameters for each isotherm including Langmuir and Freundlich isotherm were determined. The experimental data were analyzed using the first-order kinetic and the second-order kinetic models. Desorption and reusability of the RS/Fe₃O₄-NCs were studied using a dilute solution of mineral acid. The optimum conditions for the sorption of Cu(II) and Pb(II) were obtained 100 and 60 mg/L of initial ion concentration, 41.96 and 59.35 s of removal time and 0.13 g of adsorbent for both ions, respectively. The adsorption data and kinetics fitted well with Langmuir isotherm and second-order kinetic model. The regeneration results confirmed that the prepared nanocomposites can offer excellent reusability from the adsorption medium. Therefore, RS/Fe₃O₄-NCs had highly removal efficiency for elimination of Cu(II) and Pb(II). Furthermore, unmodified rice straw (RS), modified rice straw (ORS) and ORS/Fe₃O₄-NCs were incorporated with polycaprolactone (PCL) in different percentages loading of the filler by solution casting method. The samples were characterized with PXRD, TEM, FESEM, EDX, FT-IR, and VSM. Mechanical and thermal properties were studied by using Instron Universal Testing Machine and thermal gravimetric analysis, respectively. ORS/PCL composites and ORS/Fe₃O₄/PCL-NCs showed superior mechanical properties due to greater compatibility of ORS and ORS/Fe₃O₄-NCs with PCL, but RS/PCL composites displayed poor adhesion between RS and PCL matrix. The tensile strength was improved with the addition of 5.0 wt.% of ORS and ORS/Fe₃O₄-NCs. The TGA showed the thermal stability of ORS/Fe₃O₄/PCL-NCs was higher than RS/PCL-Cs and ORS/PCL-Cs. The antibacterial activities of ORS/Fe₃O₄-NCs in PCL matrix was investigated against Gram-negative and Gram-positive bacteria by the disc diffusion method. The results showed the strong antibacterial activity against Gram-negative and Gram-positive bacteria, and it was increased with the increasing amount of Fe₃O₄-NPs. In conclusion, the nanocomposites of natural fibers show good potential in the field of nanotechnology for development of reliable and ecofriendly processes.